How Good at Neurology are you? – Answers. Issue 5 (1st October 2003) - Goldsmith, Paul; Lennox, Graham; Ray, Julian
Abstract : 1. This patient has unconsiousness of undetermined origin. (a) and (b) are therefore not options. Indeed her EEG does show some activity, although a flat EEG does not mean the patient is dead. The EEG shows burst suppression – periods of flatness followed by some brief activity. The mechanism is not well understood but probably reflects dominance of subcortical and particularly thalamic generated rhythms. The burst-suppression pattern of the EEG is seen in adults in a rather limited number of conditions. It is a recognised feature in deep stages of general anaesthesia, it can occur following cardiorespiratory arrest, and is seen in conjunction with sedative overdose. Further Reading Niedermeyer E, Sherman DL, Geocadin RJ, Hansen HC, Hanley DF (1999) The Burst Suppression EEG. Clinical EEG (electroencephalography), 3, 99–105. 2. Paget's disease. He has cataracts and prostatic outflow obstruction, common pathologies in older people. However, his deafness and back pain are